Stability and Hydrolysis Constants of N-Hydroxyethyliminodiacetates of the Rare Earths - F. Chastellain; André E. Merbach (CHIMIA)
The stability constants for the 1:1 and 1: 2 complexes formed between the tetradentate ligand N-hydroxyethyliminodiacetate (HIMDA) and the rare earth ions have been determined at 20°C and at a metal concentration of 0.1 M. The hydrolysis of the 1: 2 complexes has been investigated at 20°C in 0.15 M rare earth solutions; the protonation constants of the M(HIMDA)2OH2- complexes have approximately the same values between La and Gd, but decrease strongly from Gd through Lu.